Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar Melalui LI-BAS KO-MAN-DO - Puspa Nurmasyitah (Perpustakaan Nasional RI, 2022)
School’s library has the some functions. One of the school’s library functions is as the source of learning. Students literate reading and writing at the library as library’s service. But not all the students have the same competencies to do basic literacy. Consequently, the students are not able to use the library as source of learning. The students have the lack of understanding in basic literacy but they are in junior high school. So that, the teacher designs the technique in learning basic literacy (LIterasi Baca tuliS) or LI-BAS by using consultation, independence, moral suggestion (KOnsultasi, MANdiri, DOrongan moral) or Ko-Man-Do. The goal of the research is helping the students who has lacked of literacy to solve their problems in learning especially reading and writing in simply. The method of the research applies qualitative-description by describing the condition of discussing objects in preceding and post condition. The data collection is by using observation and interview. The data be analyzed by description of reading and writing competencies based on the categories. The research subjects consist of 4 students who have lacked of understanding in basic literacy. The result of research shows that increasing in basic literacy –reading and writing- after application of the Ko-Man-Do technique. The students be able to read words, phrases, sentence and paragraph. The enhancement of the research is about 38% in average. The final discussion reveals that the Ko-Man-Do technique potentially increase student’s ability in basic literacy – reading and writing – in the school’s library.